2004
DOI: 10.1038/sj.bmt.1704466
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mobilisation failure in patients with non-Hodgkin's lymphoma

Abstract: Summary:Factors affecting progenitor cell mobilisation in patients with non-Hodgkin's lymphoma (NHL) are incompletely understood. We have analysed factors predicting mobilisation failure in 97 consecutive patients with NHL (59 males, 38 females; median age 49 years) who received mobilisation with intermediate- dose þ cells. In all, 18 patients (19%) failed to reach this threshold. In univariate analysis, premobilisation factors associated with mobilisation failure included BM involvement at the time of diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
108
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 28 publications
4
108
0
5
Order By: Relevance
“…Overall, the patients were characterized by features that are known to affect standard stem cell mobilization negatively, including advanced age, a diagnosis of NHL, previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, previous autoSCT, or failure of at least one previous attempt at mobilization [7][8][9][10][11][12][13][14][15]. We observed that, despite these unfavorable characteristics, mobilization with plerixafor and G-CSF enabled the required number of stem cells to be collected in 67.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the patients were characterized by features that are known to affect standard stem cell mobilization negatively, including advanced age, a diagnosis of NHL, previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, previous autoSCT, or failure of at least one previous attempt at mobilization [7][8][9][10][11][12][13][14][15]. We observed that, despite these unfavorable characteristics, mobilization with plerixafor and G-CSF enabled the required number of stem cells to be collected in 67.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors are known to affect the outcome of stem cell mobilization negatively in the context of traditional mobilization regimens that are based on the administration of G-CSF with or without chemotherapy. These factors include advanced age, a diagnosis of non-Hodgkin's lymphoma (NHL), previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, and the failure of at least one previous attempt at mobilization [7][8][9][10]. In this study, we decided to investigate whether the above-mentioned factors might allow the prediction of a suboptimal outcome for stem cell mobilization with plerixafor and G-CSF.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] However, the value of patient characteristics and prior treatment clinical factors to successfully score and accurately predict the risk of poor mobilization is controversial, and recent studies do suggest that they are inaccurate predictors and should not be used to identify candidates for optimized strategies to prevent mobilization failure. 17,18 At present, the measurement of preapheresis levels of CD34+ cells in PB 7,[19][20][21][22] is the most robust and recommended indicator to identify potential poor mobilizers and efficiently rescue them with novel mobilization strategies, including the use of plerixafor.…”
Section: Introductionmentioning
confidence: 99%
“…Although poor mobilizers are difficult to identify in advance, the following risk factors for poor mobilization are accepted in general: age 460 years, progressive disease, severe BM involvement, previous chemo-and/or radiotherapy, type of chemotherapy, previously failed mobilization attempts, platelet counts o100 Â 10 9 /L before apheresis and the occurrence of neutropenic fever during mobilization. 3,[9][10][11][12][13] The bicyclam plerixafor (formerly known as AMD3100) was found to interrupt the interaction between the chemokine stroma-derived factor-1 alpha, which is constitutively expressed on BM stromal cells, 14,15 and its cognate receptor CXCR4 on CD34 þ HSC, 16 resulting in a rapid increase of PBSC. 12 Initially designed as a CXCR4 entry-inhibitor for the treatment of HIV-1 infections, 17 the transient leukocytosis monitored in healthy individuals, as well as in HIV positive patients, led to a change in its use.…”
Section: Introductionmentioning
confidence: 99%